PELATIHAN PENGENALAN KECERDASAN BUATAN DAN MACHINE LEARNING DENGAN GOOGLE'S TEACHABLE MACHINE BAGI SISWA SEKOLAH MENENGAH - Kasih, Kasih Kasih; Santoso, Bodi; Uliyatunisa, Uliyatunisa (KOMMAS: Jurnal Pengabdian Kepada Masyarakat, 2025)
The introduction of Artificial Intelligence (AI) among secondary school students, particularly at Cahaya Kasih Educational Institution in Bojongsari Baru, remains limited, even though AI has become increasingly important across various fields. The rapid advancement of AI and Machine Learning (ML) technologies has significantly influenced many aspects of human life. This situation may create a digital literacy gap between young generations and the competencies required in the modern era. This Community Service Program (PKM) aims to provide a solution through a training activity on AI and ML introduction using Google’s Teachable Machine. This platform was selected because it is web-based, easy to use, and allows students to build simple AI models without requiring complex programming skills. The program involved 20 participants aged between 12 and 17 years. The implementation methods included surveys and interviews with teachers and students, supported by stages of observation, reflection, and data collection related to learning and technology application. In addition, a literature review was conducted to provide a strong theoretical foundation so that the implementation could be scientifically accountable. The primary goal of this activity is to improve students’ digital literacy through the development of simple AI models. The results show that most participants were satisfied with the training, with around 85% expressing a strong interest in learning more about AI. The students’ projects successfully recognized objects and sounds with good accuracy, indicating an improvement in their understanding of AI concepts. Therefore, this activity is expected to help educational partners overcome limitations in technological understanding while contributing to the development of a younger generation that is better prepared to face the challenges of the AI era. Keywords: Artificial Intelligence, Machine Learning, Teachable Machine, Digital Literacy